Nonphytate Phosphorus Requirement and Phosphorus Excretion of Broiler Chicks Fed Diets Composed of Normal or High Available Phosphate Corn as Influenced by Phytase Supplementation and Vitamin D Source - Yan, F.; Waldroup, P.W. (International Journal of Poultry Science, 2006)
A study was conducted to evaluate the ability of young broiler chicks (0-3 wk) to utilize the P provided by a high available phosphate corn (HAPC) in comparison with yellow dent corn (YDC) and to determine the extent to which microbial phytase supplementation and use of 25-hydroxycholecalciferol (25-OH-D3) in the diet could reduce the requirements for P and subsequently reduce P excretion. Diets were prepared using either YDC or HAPC, which contained about the same total P but differed in phytate-bound P content. Within each corn type, diets were fortified with either vitamin D3 or 25-OH-D3 at the rate of 68.9 μg/kg diet. Treatment diets were prepared by varying the amount of dicalcium phosphate and ground limestone, and ranged from 0.09 to 0.50% nonphytate P (nPP) for YDC diets and 0.18 to 0.50% nPP for HAPC diets. Sublots of each diet were supplemented with 1000 units/kg phytase. Each diet was fed to four replicate pens of six male broilers of a commercial strain from 1 to 21 d of age. After factorial analysis, nonlinear regression analysis was conducted to estimate a nPP level sufficient for maximum body weight gain or tibia ash percentage for each corn type as influenced by phytase supplementation or use of 25-OH-D3. For broilers fed YDC diets, the estimations for maximum tibia ash were 0.40, 0.35, 0.32, and 0.27% nPP for diets supplemented with D3, D3 + phytase, 25-OH-D3, and 25-OH-D3 + phytase respectively. For broilers fed HAPC diets, substitution of D3 with 25-OH-D3 had no significant effect on tibia ash percentage and the inflection points for maximum tibia ash were 0.39 and 0.33% with and without phytase supplementation respectively. These nPP levels were sufficient to support body weight, feed conversion, or livability. The nPP in HAPC was equivalent in bioavailability to the P from dicalcium phosphate. In the absence of phytase, dry feces of broiler chicks fed YDC diets at the NRC (1994) recommended level of 0.45% nPP contained 1.19% P, whereas at the above inflection points, the fecal P content was 1.06, 1.11, 0.98, and 0.78% for chicks fed YDC diets supplemented with D3, D3 + plus phytase, 25-OH-D3, and 25-OH-D3 + phytase respectively. For chicks fed HAPC diets at the inflection points, the fecal P content was 0.84 and 0.68% with and without phytase supplementation respectively. Thus fecal P output can be reduced significantly while maintaining optimum live performance and bone mineralization by supplementation with microbial phytase, addition of 25-OH-D3, use of HAPC, reduction in dietary nPP level, or combinations of the above.